Personal Hygiene pada Pedagang Makanan Siap Saji di Desa Latta Kecamatan Teluk Ambon Baguala - M Fadly Kaliky; Rahma Tunny (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Personal hygiene can affect food contamination can be for several factors including the cleanliness of eating utensils because the human body can also be a source of pollution including eating utensils if they do not maintain cleanliness. Contamination does not only occur in food and water sources, but food equipment that does not meet health requirements is also a cause. In Indonesia, regulations have been made in the form of Regulation of the Minister of Health of the Republic of Indonesia No. 1096 / Menkes / SK / VI / 2011 that for the requirements for hygiene and sanitation of catering services. Based on the description above, the problem in the study can be formulated, namely how is personal hygiene in fast food in Latta Village, Teluk Ambon Baguala District. To find out Personal hygiene in fast food in Latta Village, Teluk Ambon Baguala District. This type of research is descriptive research by interviewing and observing. The population in this study was 22 fast food traders. The sample used was 5 (five) fast food traders in Latta Village. The results of the study have been carried out that the examination of five traders I, traders II, traders III, traders IV, and traders V with the criteria did not meet the requirements according to Permenkes No. 1096/Menkes/Per/VI/2011 namely 0 CFU The results obtained were five food handlers for personal hygiene did not meet the requirements in Latta Village, Teluk Ambon Baguala District. The five samples met the requirements and five food handlers in Latta Village, Teluk Ambon Baguala District had Personal Hygiene that did not meet the requirements. The five samples met the requirements and five food handlers in Latta Village, Teluk Ambon Baguala District had Personal Hygiene that did not meet the requirements.